2000
DOI: 10.1046/j.1432-1327.2000.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

The N‐terminal portion of the main cytosolic loop mediates K+sensitivity in the retinal rod Na+/Ca2+‐K+‐exchanger

Abstract: Two types of Na+/Ca2+‐exchangers have been characterized in the literature: The first is the cardiac, skeletal muscle and brain type, which exchanges 1 Ca2+ for 3 Na+, the second, found in retinal photosensor cells, transports 1 Ca2+ and 1 K+ in exchange for 4 Na+. The present work describes the properties of chimeric constructs of the two exchanger types. Ca2+ gel overlay experiments have identified a high affinity (Kd in the 1 µm range) Ca2+‐binding domain between Glu601 and Asp733 in the main cytosolic loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(63 reference statements)
1
5
1
Order By: Relevance
“…Such a result is consistent with the now established notion that the phylogenetically conserved and Na ϩ /Ca 2ϩ exchanger superfamily defining ␣-repeat elements form the ion transport binding pocket (9,43). On the other hand, it is in contradiction to two reports published recently that suggested that either another subunit was required for K ϩ -dependent operation of bovine NCKX1 (25) or that a segment of the proposed intracellular loop of NCKX1 was an essential part of the K ϩ -binding site (44). It is likely that contaminating currents confounded the first of these reports, whereas allosteric regulation of activity may have accounted for the second.…”
Section: Fig 8 Ksupporting
confidence: 86%
“…Such a result is consistent with the now established notion that the phylogenetically conserved and Na ϩ /Ca 2ϩ exchanger superfamily defining ␣-repeat elements form the ion transport binding pocket (9,43). On the other hand, it is in contradiction to two reports published recently that suggested that either another subunit was required for K ϩ -dependent operation of bovine NCKX1 (25) or that a segment of the proposed intracellular loop of NCKX1 was an essential part of the K ϩ -binding site (44). It is likely that contaminating currents confounded the first of these reports, whereas allosteric regulation of activity may have accounted for the second.…”
Section: Fig 8 Ksupporting
confidence: 86%
“…These studies raise the issue of whether the rod NCKX cDNA alone is sufficient for Na/Ca-K exchange activity observed in situ. Moreover, a recent study shows that potassium sensitivity can be conferred on heart NCX1 by inserting an N-terminal portion of the large cytosolic loop of bovine rod NCKX into the large cytosolic loop of heart NCX1; the authors interpret these data to indicate that the N-terminal portion of the rod NCKX cytosolic loop is the site of potassium transport in bovine rod NCKX (11). Significantly, cone NCKX and other NCKX paralogs do not appear to contain a related domain.…”
mentioning
confidence: 99%
“…As discussed above, the various members of the NCKX gene family only share sequence identity in the two sets of TMs comprising about 320 residues or only 26% of the total bovine rod NCKX1 sequence. Moreover, it has been suggested that the site coding for K + dependence and K + transport is located on part of the cytosolic loop of bovine rod NCKX1,22 a domain not found in cone NCKX2 or in NCKX sequences from lower organisms. Thus, it is important to establish that the various NCKX cDNAs indeed code for Na/Ca exchangers that not only require K + but also transport K + .…”
Section: Resultsmentioning
confidence: 99%
“…A surprising feature of the bovine heart NCX1‐dolphin rod NCKX1 chimera was that the activity in K + medium was always markedly higher than that in Li + medium. This may be consistent with observations by Seiler et al ., who suggest that K + dependence and K + transport are located on part of the cytosolic loop of bovine rod NCKX1 22. Therefore, we examined whether Ca 2+ uptake via reverse Na/Ca(‐K) exchange was associated by K + transport as measured with the K + congener 86 Rb.…”
Section: Resultsmentioning
confidence: 99%